Holocene vegetation, fire and climate interactions on the westernmost fringe of the Mediterranean Basin - Morales-Molino, César; García-Antón, Mercedes; Postigo-Mijarra, José M; Morla, Carlos (Quaternary Science Reviews, 2013)
A new palaeoecological sequence from the western Iberian Central Range signiﬁcantly contributes to the knowledge on the Holocene vegetation dynamics in central Iberia. This sequence supports the existence of time-transgressive changes in the vegetation cover during the beginning of the Holocene over these central Iberian mountains, speciﬁcally the replacement of boreal birchepine forests with Mediterranean communities. Anthracological analyses also indicate the replacement of boreal pines (Pinus sylvestris) with Mediterranean ones (Pinus pinaster) during the early Holocene. The observed vegetation changes were generally synchronous with climatic phases previously reconstructed for the western Mediterranean region, and they suggest that the climatic trends were most similar to those recorded in the northern Mediterranean region and central Europe. Several cycles of secondary succession after ﬁre ending with the recovery of mature forest have been identiﬁed, which demonstrates that the vegetation of western Iberia was highly resilient to ﬁre disturbance. However, when the recurrence of ﬁre crossed a certain threshold, the original forests were not able to completely recover and shrublands and grasslands became dominant; this occurred approximately 5800e5400 cal yr BP. Afterwards, heathlands established as the dominant vegetation, which were maintained by frequent and severe wildﬁres most likely associated with human activities in a climatic framework that was less suitable for temperate trees. Finally, our palaeoecological record provides guidelines on how to manage protected areas in Mediterranean mountains of southwestern Europe, especially regarding the conservation and restoration of temperate communities that are threatened there such as birch stands.
Keywords: Betula; charcoal; Fire ecology; Forest management; Heathlands; macrofossils; pollen; Spain